Systematic Literature Review : Perbandingan Algoritma Round Robin dan Shortest Job First dalam Penjadwalan CPU - Fadhilah, Ibnu; Siregar, Herbert (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2025)
The Central Processing Unit (CPU) scheduling is a crucial aspect of operating systems that significantly impacts overall system efficiency. Round Robin (RR) and Shortest Job First (SJF) are two commonly used scheduling algorithms, each with distinct characteristics. Although numerous studies have compared these algorithms, a clear consensus on the superiority of either algorithm across various workload scenarios remains elusive. This systematic literature review aims to analyze and synthesize empirical evidence from prior research (2020-2024) comparing the performance of RR and SJF algorithms. Literature searches on four major databases and study selection using the PRISMA framework with strict inclusion criteria (empirical comparative studies from 2020-2024) yielded eight articles for analysis. The synthesis of results indicates that the SJF algorithm, particularly its preemptive variant (SRTF), consistently excels in efficiency, with an Average Waiting Time (AWT) that can be over 50% lower than RR in some scenarios. Conversely, RR demonstrates superiority in response time and fairness in CPU allocation, though its performance is highly dependent on the time quantum size. The selection of an optimal algorithm is highly contingent upon system performance metric priorities, and these findings provide a foundation for the future development of hybrid algorithms.